Hubungan Sikap, Tanggung Jawab dan Motivasi dengan Hasil Belajar Tematik Kelas V SDN 18 Pontianak Timur - Ghofur, Abdul; Martono, Martono; Halidjah, Siti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The objective of this study is to examine the correlation between learning attitude, learning responsibility, and learning motivation, and their impact on learning outcomes in theme learning at Sekolah Dasar Negeri 18 Pontianak Timur. The research methodology employed in this study is a descriptive approach, specifically utilizing a style of research known as correlation studies. The present study employed a sample of 33 kids who were in the fifth grade. The data gathering methods employed in this study encompass document analysis techniques and indirect communication approaches, which involve establishing indirect connections or utilizing intermediary instruments, such as questionnaires. The instruments employed for data collection encompass learning attitude surveys, learning responsibility questionnaires, and learning motivation questionnaires. The study employs descriptive statistical analysis to conduct data analysis techniques and examines the association between learning attitudes, learning responsibilities, and learning motivation with student learning outcomes. The investigation utilizes simple correlation analysis and multiple correlations, facilitated by the SPSS application version 25. The study's findings indicate a statistically significant and positive correlation between learning attitude, learning responsibility, and learning motivation, and the thematic learning outcomes of fifth-grade students at Sekolah Dasar Negeri 18 Pontianak Timur. The correlation coefficient of 0.763 suggests a strong relationship. This implies that when students possess high levels of learning attitude, learning responsibility, and learning motivation, their learning outcomes tend to be high. Conversely, when these factors are low, learning outcomes are likely to be low as well.